Advances in atomic, molecular, and optical physics. - Bederson, Benjamin; Walther, H. (Herbert), 1935-2006 (Advances in atomic, molecular, and optical physics, 1998)
Praise for the Series "This volume maintains the authoritative standards of the series ... The editors and publishers are to be congratulated."--M.S. Child in Physics Bulletin "Maintains the high standards of earlier volumes in the series ... All the articles are written by experts in the field, and their summaries are most timely ... Strongly recommended."--G. Herzberg in American Scientist